Major companies of Europe 1985 volume 1 : companies in the European Economic Community - Whiteside, R. M. (London, 1985)
The book contains many of the largest companies in the world. the area covered by volume 1, the European Economic Community, represents a rich consumer market of 270 million people. Over one third of the world's imports and exports are channelled through the EEC. The Community represents the world's largest integrated market.
Includes index
usc 05/11/2021
Ref.
Keywords: Industries; Corporations; European Economic Community countries; Europe